Expanding the phenotype of TAB2 variants and literature review. Issue 11 (16th August 2022) - Woods, Emily; Marson, Imogen; Coci, Emanuele; Spiller, Michael; Kumar, Ajith; Brady, Angela; Homfray, Tessa; Fisher, Richard; Turnpenny, Peter; Rankin, Julia; Kanani, Farah; Platzer, Konrad; et al.
Abstract: TAB2 is a gene located on chromosome 6q25.1 and plays a key role in development of the heart. Existing literature describes congenital heart disease as a common recognized phenotype of TAB2 gene variants, with evidence of a distinct syndromic phenotype also existing beyond this. Here we describe 14 newly identified individuals with nine novel, pathogenic TAB2 variants. The majority of individuals were identified through the Deciphering Developmental Disorders study through trio whole exome sequencing. Eight individuals had de novo variants, the other six individuals were found to have maternally inherited, or likely maternally inherited, variants. Five individuals from the same family were identified following cardiac disease gene panel in the proband and subsequent targeted familial gene sequencing. The clinical features of this cohort were compared to the existing literature. Common clinical features include distinctive facial features, growth abnormalities, joint hypermobility, hypotonia, and developmental delay. Newly identified features included feeding difficulties, sleep problems, visual problems, genitourinary abnormality, and other anatomical variations. Here we report 14 new individuals, including novel TAB2 variants, in order to expand the emerging syndromic clinical phenotype and provide further genotype–phenotype correlation.